2017
DOI: 10.3389/fpls.2017.01075
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Three L-Asparaginases from Maritime Pine (Pinus pinaster Ait.)

Abstract: Asparaginases (ASPG, EC 3.5.1.1) catalyze the hydrolysis of the amide group of L-asparagine producing L-aspartate and ammonium. Three ASPG, PpASPG1, PpASPG2, and PpASPG3, have been identified in the transcriptome of maritime pine (Pinus pinaster Ait.) that were transiently expressed in Nicotiana benthamiana by agroinfection. The three recombinant proteins were processed in planta to active enzymes and it was found that all mature forms exhibited double activity asparaginase/isoaspartyl dipeptidase but only PpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…In fact, the release of urea and ornithine through the action of ARG and subsequent catabolism, in coordination with the activity of P5CDH, could provide not only ammonium but also glutamate for GS1b activity ( Cañas et al, 2008 ). Asparagine is also important in N storage and mobilization in pine ( Canales et al, 2012 ), and the observed decrease in the abundance of ASPG transcripts is consistent with the homeostasis of asparagine ( Van Kerckhoven et al, 2017 ; Figure 7 ).…”
Section: Discussionsupporting
confidence: 63%
“…In fact, the release of urea and ornithine through the action of ARG and subsequent catabolism, in coordination with the activity of P5CDH, could provide not only ammonium but also glutamate for GS1b activity ( Cañas et al, 2008 ). Asparagine is also important in N storage and mobilization in pine ( Canales et al, 2012 ), and the observed decrease in the abundance of ASPG transcripts is consistent with the homeostasis of asparagine ( Van Kerckhoven et al, 2017 ; Figure 7 ).…”
Section: Discussionsupporting
confidence: 63%